Reformulating the Policy Framework for Sting Operations by Investigators of the Corruption Eradication Commission - Bonde, Elsa; Ibrahim, Aji Lukman (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2025)
Corruption offenses in Indonesia are perceived as ongoing and persistent, continuing to this day and resulting in significant losses to the state. The establishment of the Corruption Eradication Commission through Law Number 30 of 2002 concerning the Corruption Eradication Commission serves as a trigger mechanism to enhance the effectiveness of anti-corruption efforts. As part of its initiatives, the Corruption Eradication Commission conducts Sting Operations aimed at combating corruption by apprehending perpetrators through silent operations. This study formulates two problems, namely, how the mechanism of Sting Operations held by the Corruption Eradication Commission investigators aligns with legislation, and what is the ideal regulation of Sting Operations held by the Corruption Eradication Commission investigators. This study is a normative legal research with secondary data consisting of primary, secondary, and tertiary legal materials. This study uses a statutory, conceptual, and interpretive approach. The result of this study indicates that Sting Operations conducted by the Corruption Eradication Commission are often equated with the concept of ‘caught red-handed’, which is stated in The Indonesian Criminal Procedure Code (KUHAP). However, both Sting Operations and ‘caught red-handed’ differ in meaning and may potentially violate the principle of due process of law. Therefore, a comprehensive reformulation of Sting Operations procedures within the legal framework of the Corruption Eradication Commission is necessary.